Efektivitas Latihan ROM Pasif Ekstremitas Bawah terhadap Percepatan Bromage Score pada Pasien Post Spinal Anestesi - Dwi Handoyo; Tri Budi Santoso; Agil Almas (Pusat Riset dan Inovasi Nasional, 2024)
Background: Spinal (subaracnoid) anesthesia is a regional anesthesia with the injection of local anesthetic drugs into the subarachnoid space. Spinal anesthesia can be given for procedures involving the lower limbs, pelvis, and perineum. Patients with spinal anesthesia are evaluated to determine whether or not the patient can be transferred to the ward. The indicator currently used is the Bromage Score, which is an indicator of the achievement of lower limb movement ability. The Bromage Score is an instrument for assessing the strength of the lower extremity muscles in patients after spinal anesthesia (Texas Children's Hospital, 2016). Full motion assessment score 0, unable to move the leg extremities score 1, unable to flex, but able to move the total leg score 2, unable to move the leg score 3. Purpose: To determine the effect of passive ROM exercises of the lower extremities with bromage score acceleration in post-spinal anesthesia patients. Research method: Using a quasi-experimental method with a posttest only control group design. The sample of this study amounted to 20 respondents, 10 respondents in the intervention group and 10 respondents in the control group. The intervention group performed passive ROM and the control group did not perform passive ROM. Sampling was done by consecutive sampling. The research instrument was an observation sheet, a watch. Results: The results of the statistical test used were Mann Whitney, after the P Value test = 0.000 (P Value <0.005). Conclusion: There is an influence between passive ROM exercises of the lower extremities and the acceleration of the bromage score in post-spinal anesthesia patients in the conscious recovery room.